Spatial mapping and assessment of nutritional status and socio demographic determinants among under-five children in a rural region of Southern Karnataka: a cross-sectional study - Kurkuri, Shweta Neminath; Kurkuri, Shraddha Neminath; Singh, Sunitha; A., Lekha Shree (International Journal Of Community Medicine And Public Health, 2025)
Background: Malnutrition remains a significant public health concern among under-five children, particularly in low- and middle-income countries. It includes both undernutrition and the rising issue of overnutrition. The objectives of the study were to assess the nutritional status of children under-five years of age and to identify socio-demographic factors influencing it. Methods: A community-based cross-sectional study was conducted among 255 under-five children. These children were selected by simple random sampling in the rural field practice area of a medical college in southern Karnataka. Anthropometric measurements were taken and nutritional status was assessed using WHO Z-score classifications. Data analysis was carried out using Epi-Info and WHO Anthro Survey Analyser. Associations were assessed using Chi-square and Fisher’s exact tests. Results: Out of 255 children, 31.76% (81) were stunted, 20% (51) were underweight and 15.69% (40) were wasted, showing significant undernutrition. Also, 9.02% (23) and 12.55% (32) were overweight/obese by weight-for-length and BMI-for-age, respectively, indicating emerging overnutrition. This reflects the double burden of malnutrition in the group. Stunting was most prevalent among children aged 1 to 2 years. Underweight and wasting were more common in boys. A significant association was noted between socioeconomic status and underweight (p=0.035), with the highest prevalence of malnutrition in Class IV. No significant associations were found between other sociodemographic details and nutritional status. Conclusions: The study reported a high burden of malnutrition, especially stunting and underweight, with an emerging trend of overweight and obesity. Socioeconomic status significantly influenced nutritional outcomes, highlighting the need for a multipronged approach.